Protein‐extending ACTN2 frameshift variants cause variable myopathy phenotypes by protein aggregation - Johanna Ranta‐aho; Kevin J. Felice; Per Harald Jonson; Jaakko Sarparanta; Cédric Yvorel; Ines Harzallah; Renaud Touraine; Lynn Pais; Christina A. Austin‐Tse; Vijay S. Ganesh; Melanie C. O'Leary; Heidi L. Rehm; et al. (Annals of Clinical and Translational Neurology)
Abstract Objective The objective of the study is to characterize the pathomechanisms underlying actininopathies. Distal myopathies are a group of rare, inherited muscular disorders characterized by progressive loss of muscle fibers that begin in the distal parts of arms and legs. Recently, variants in a new disease gene, ACTN2, have been shown to cause distal myopathy. ACTN2, a gene previously only associated with cardiomyopathies, encodes alpha‐actinin‐2, a protein expressed in both cardiac and skeletal sarcomeres. The primary function of alpha‐actinin‐2 is to link actin and titin to the sarcomere Z‐disk. New ACTN2 variants are continuously discovered; however, the clinical significance of many variants remains unknown. Thus, lack of clear genotype–phenotype correlations in ACTN2‐related diseases, actininopathies, persists. Methods Functional characterization in C2C12 cell model of several ACTN2 variants is conducted, including frameshift and missense variants associated with dominant and recessive actininopathies. We assess the genotype–phenotype correlations of actininopathies using clinical data from several patients carrying these variants. Results The results show that the missense variants associated with a recessive form of actininopathy do not cause detectable alpha‐actinin‐2 aggregates in the cell model. Conversely, dominant frameshift variants causing a protein extension do form alpha‐actinin‐2 aggregates. Interpretation The results suggest that alpha‐actinin‐2 aggregation is the disease mechanism underlying some dominant actininopathies, and thus, we recommend that protein‐extending frameshift variants in ACTN2 should be classified as pathogenic. However, this mechanism is likely elicited by only a limited number of variants. Alternative functional characterization methods should be explored to further investigate other molecular mechanisms underlying actininopathies.